The Madrid Socialist Federation in the Decades of the Eighty Ninety. Stability and Access to Government Regional (Global Journal of Human-Social Science, 2023)
The Madrid Socialist Federation FSM has been one of the most important organizations of the Spanish Socialist Workers Party PSOE at least in the last decades of the 20th century Its main hallmark is the lack of internal stability caused by the existence of various sectors within it a fact that caused internal conflicts in the 1970s Joaqu n Leguina s arrival at the Regional Secretariat marked the beginning of a period of relative calm in the Madrid socialist organisation during the 1980s during which Leguina became president of the Autonomous Community of Madrid CAM Stability lasted a short time at the FSM The 1990s witnessed once again the return to internal conflicts in the Madrid organisation
Keywords: FSM; joaquín leguina; PSOE